DRAFT REVISED CODE OF PRACTICE ISSUED UNDER SECTION 377A OF THE PROCEEDS OF CRIME ACT 2002 : INVESTIGATIVE POWERS OF PROSECUTORS.: INVESTIGATIVE POWERS OF PROSECUTORS. (October 2017) - Great Britain., Attorney-General,; Northern Ireland., Office of the Attorney General,
No abstract available